A gombatermesztés szerepe az átalakuló magyar mezőgazdaságban - Horváth, Gábor (Acta Agraria Debreceniensis, 2002)
The structure of Hungarian agriculture should be changed before the EU accession. The new structure should fulfill EU requirements and also produce competitive products. Unconventional products (mushroom, fish, honey etc.) have a lot of advantages: they can be produced on small farms, their trade is mainly free of regulation and their markets are almost unlimited. This paper deals with one of these alternative agricultural enterprises, namely mushroom production. Hungarian mushroom production – in spite of difficulties – has witnessed remarkable expansion: it has increased its production by fourfold and its export by fivefold in less than ten years. The low level of wages gives Hungary significant advantage over its competitors. If we could ensure the appropriate infrastructure (technical advice, bank loans, etc.) the mushroom industry would become one of the most profitable sectors of Hungarian agriculture.